2011
DOI: 10.1007/s11031-010-9200-y
|View full text |Cite
|
Sign up to set email alerts
|

Binge eating as a consequence of unfulfilled basic needs: The moderating role of implicit achievement motivation

Abstract: The present study hypothesized that unfulfilled basic needs for autonomy, competence and relatedness (SDT, Deci and Ryan, Psychol Inq 11:227 268, 2000) are associated with the impulse to eat and with binge eating. In addition, we assumed that individuals with a high achievement motive, who are characterized by high selfcontrol competences, have the same impulse to eat when confronted with unfulfilled basic needs, but are better able to control the impulse to binge eat than individuals with a low achievement m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 43 publications
2
25
1
Order By: Relevance
“…The reason why the ACH × ComSat interaction did not predict exercise addiction could be that individuals with a high achievement motive are characterized by high self-control skills, which may protect them from becoming addicted even when their need for competence is thwarted (Schüler & Kuster, 2011). Thus, a third variable (self-control) is likely to have overridden the expected interaction effect.…”
Section: Discussionmentioning
confidence: 98%
“…The reason why the ACH × ComSat interaction did not predict exercise addiction could be that individuals with a high achievement motive are characterized by high self-control skills, which may protect them from becoming addicted even when their need for competence is thwarted (Schüler & Kuster, 2011). Thus, a third variable (self-control) is likely to have overridden the expected interaction effect.…”
Section: Discussionmentioning
confidence: 98%
“…However, a few previous studies that relied on betweenperson designs demonstrated that psychological need satisfaction is implicated in one's eating behaviors. Between-person differences in need satisfaction were found to be associated with a healthier diet, such as a higher intake of fruits and vegetables (see Ryan, Patrick, Deci, & Williams, 2008 for an overview), whereas psychological need frustration was related to more unhealthy weight control behaviors (Thogerson-Ntoumani, Ntoumanis, & Nikitaras, 2010), more eating disorder symptoms (Bartholomew et al, 2011), and more binge eating behaviors (Schüler & Kuster, 2011;Verstuyf, Vansteenkiste, & Soenens, 2012).…”
Section: Self-determination Theory: the Role Of Basic Psychological Nmentioning
confidence: 99%
“…There is some indirect evidence for this moderation hypothesis. For instance, Schüler and Kuster (2011) found that the association between unfulfilled needs and binge eating was present for people low in achievement motivation, but not for those high in achievement motivation. As people high in achievement motivation have high self-control capacities (Mischel, 1961), Schüler and Kuster argued that differences in self-control could account for this moderation effect.…”
Section: The Moderating Role Of General Self-control Strength and Emomentioning
confidence: 99%
See 2 more Smart Citations